Locally made paediatric rehabilitation and seating systems for cerebral palsy children in Sarawak - Ling, Sui Hui (Universiti Kebangsaan Malaysia, 2011)
Children with cerebral palsy (CP) are often prescribed Rehabilitation and Seating Systems (RSS) to assist in daily activities, posture improvement and prevention of muscular-skeletal complications. In Sarawak, a special project to produce RSS was started under a partnership of a Japanese physiotherapist, health department and the community using local material.